Vitamine D supply in girls of puberty age with autoimmune hepatitis - E. F. Сhaykivska; V. S. Berezenko; T. F. Tatarchuk (Kazimierz Wielki University, 2020)
Vitamin D undergoes important biotransformation and inactivation in the liver. Because vitamin D is metabolized in the liver, abnormal vitamin D metabolism can be expected to be associated with chronic liver disease, including autoimmune hepatitis (AIH). The prevalence of vitamin D deficiency in puberty was the justification for the objective of the study- to determine the characteristics of vitamin D supply in girls of puberty age with AIH with autoimmune hepatitis during this period. Materials and methods. To solve this goal, a comprehensive clinical and paraclinical examination of 66 girls withAIH and 180 relatively healthy girls of the control group aged 12-17 years. The complex included clinical and anamnestic data, biochemical study of liver function, determination of serum autoantibodies and markers of viral hepatitis, the level of 25- (OH) D in blood serum, ultrasound and elastography of the hepatobiliary system organs, liver biopsy. Results. The mean level of vitamin 25 (OH) D in the serum of girls with AIH of pubertal age was 17.14 ± 1.06 vs. 23.27 ± 0.53 ng / ml in the control (p<0,01). In 66.67% of patients with AIH there was a deficiency of 25 (OH) D, in 22.73% - insufficiency, in 10.61% - the optimal level. The supply of vitamin D depended on the histological activity of AIG. Among girls with AIH and histological activity index> 9 points, the share of patients with vitamin D deficiency was 79.41% compared with 53.13% of cases among girls with AIH, where the histological activity index was <9 points (χ2=5.13; p<0,02). Conclusions. Cytolysis, cholestasis, mesenchymal-inflammatory syndrome, hepatocellular insufficiency in AIH in girls of puberty agedevelops against the background of reduced vitamin D supply, which depends on the histological activity of the disease.